Addressing the diversity of Xylodon raduloides complex through integrative taxonomy - Javier Fernández-López; M. Teresa Telleria; Margarita Dueñas; Andrew W. Wilson; Mahajabeen Padamsee; Peter K. Buchanan; Gregory M. Mueller; María P. Martín (IMA Fungus)
Abstract In this study, the taxonomic diversity of the Xylodon raduloides species complex (Hymenochaetales, Basidiomycota) is examined. Specimens were studied using an integrative taxonomic approach that includes molecular phylogenetic and morphological analyses, and environmental niche comparisons. Four different species were found inside the Xylodon raduloides complex, with a biogeographic distribution pattern bound by geographic regions: Europe, North America, Patagonia, and Australia–New Zealand. Molecular, morphological, and environmental evidences delimit two lineages within this complex: a Northern Hemisphere clade with longer basidiospores and wider ranges in temperature and precipitation tolerance, and a Southern Hemisphere clade with smaller and more spherical basidiospores, and an isothermal and more humid climate preference. The integrative taxonomic approach used in this study demonstrates congruence between data sets and shows how morphological and environmental characteristics contribute to the differentiation of fungal species complexes. By combining various sources of taxonomic information, three new species are described: Xylodon laurentianus, X. novozelandicus, and X. patagonicus.